Introduction of unshaped refractories in the wear lining of steel ladles - Etienne, F. (Kovine zlitine tehnologije, 1997)
Steel ladles are essential tools in steelmaking . In the past, research was almost entirely centered on converters but nowadays attention has focused on ladles. The determining factor for the choice of a lining is the cost per tonne of steel as well as reliability, security availability and metal purity. The cost per tonne of steel has now reached a constant level with shaped products and can hardly be improved. The introduction of new technology and radical changes are the only possible means to make the improvements in the economic situation. The application of unshaped products to the ladle may provide a solution. Experience in Japan has shown that improvements are possible when techniques utilising monolithics in ladles are adapted. Here we intend to describe the trials carried out by Lafarge Réfractaires Monolithiques and the first significant industrial results with the use of monolithic ladles in European conditions.
Keywords: jeklarstvo; ponovce; Metallurgical and Materials Engineering; metalurgija; ognjevzdržni materiali